Pengaturan Waralaba Di Indonesia: Perspektif Hukum Bisnis - Muchtar Riva’i (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2012)
The law arrangement of franchise law was first explicitly regulated by the Government Regulation No. 16 of 1997 which is then updated by Government Regulation No. 42 of 2007 to be created in an agreement that at least contains clauses as stipulated by Article 5 of the Government Regulation. However, franchise arrangements also associated with a variety of other laws and regulations applicable in Indonesia. This article is going to state that the importance of partnerships with small and medium enterprises as an effort to encourage the involvement of the wider economic community.